2021
DOI: 10.3389/fimmu.2021.741268
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of sIL-2R, TNF-α and PCT for Sepsis Infection in Patients With Closed Abdominal Injury Complicated With Severe Multiple Abdominal Injuries

Abstract: ObjectiveWe aimed to evaluate the diagnostic value of soluble interleukin-2 receptor (sIL-2R), tumor necrosis factor-α (TNF-α), procalcitonin (PCT), and combined detection for sepsis infection in patients with closed abdominal injury complicated with severe multiple abdominal injuries.Patients and MethodsOne hundred forty patients with closed abdominal injury complicated with severe multiple abdominal injuries who were diagnosed and treated from 2015 to 2020 were divided into a sepsis group (n = 70) and an inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…IL-17 is recognized as a hallmark molecule of CD4 + T helper 17 (Th17) cells, 16 and IL-2 is a marker of strong and long-lasting activation within the lymphocyte immune responses. 17 Significant increases in peritoneal levels of IL-17 and IL-2 can interact with other proinflammatory cytokines, especially TNF-α, IL-1β, and IL-6, to drive an amplified immune response, and contribute to the development of sepsis. 18 According to our finding, higher levels of peritoneal IL-1β, IL-6, TNF-α, IL-17, and IL-2 observed in this study may support the idea that the abdomen can mount a pro-inflammatory response while avoiding a state of immune paralysis, which may a dominant anti-inflammatory cytokine response pattern after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 is recognized as a hallmark molecule of CD4 + T helper 17 (Th17) cells, 16 and IL-2 is a marker of strong and long-lasting activation within the lymphocyte immune responses. 17 Significant increases in peritoneal levels of IL-17 and IL-2 can interact with other proinflammatory cytokines, especially TNF-α, IL-1β, and IL-6, to drive an amplified immune response, and contribute to the development of sepsis. 18 According to our finding, higher levels of peritoneal IL-1β, IL-6, TNF-α, IL-17, and IL-2 observed in this study may support the idea that the abdomen can mount a pro-inflammatory response while avoiding a state of immune paralysis, which may a dominant anti-inflammatory cytokine response pattern after surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Zhai et al demonstrated the good diagnostic value of PCT in sepsis closed abdominal injury infection. 34 Thus, PCT was of great significance in sepsis diagnosis and mortality prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SIRI has been widely considered in disease diagnosis and prognosis evaluation in recent years. [8][9][10][11] Topkan et al 12 have found that SIRI could be a novel, sound, and independent predictor of survival outcomes in patients with newly diagnosed glioblastoma multiforme who underwent postoperative Stupp protocol. The inflammatory prognostic index (IPI) establishes a new inflammatory prognostic model, which is an independent risk factor for the survival and prognosis of patients with non-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%